2019
DOI: 10.1093/annonc/mdy495
|View full text |Cite
|
Sign up to set email alerts
|

Development of tumor mutation burden as an immunotherapy biomarker: utility for the oncology clinic

Abstract: BackgroundTreatment with immune checkpoint blockade (ICB) with agents such as anti-programmed cell death protein 1 (PD-1), anti-programmed death-ligand 1 (PD-L1), and/or anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) can result in impressive response rates and durable disease remission but only in a subset of patients with cancer. Expression of PD-L1 has demonstrated utility in selecting patients for response to ICB and has proven to be an important biomarker for patient selection. Tumor mutation bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
1,675
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,007 publications
(1,817 citation statements)
references
References 103 publications
(95 reference statements)
28
1,675
3
6
Order By: Relevance
“…More than 50% of solid cancers sooner or later escape control of standard treatments. Those tumors with high mutational burden are easily treated with immunotherapy, which is almost ineffective in another half of cases in which specific driver genes are supposed to lead therapy resistance . However, molecular‐based recommended therapies have almost unfulfilled expectation.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of solid cancers sooner or later escape control of standard treatments. Those tumors with high mutational burden are easily treated with immunotherapy, which is almost ineffective in another half of cases in which specific driver genes are supposed to lead therapy resistance . However, molecular‐based recommended therapies have almost unfulfilled expectation.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty‐four trials were identified in the search, which have a total estimated enrollment of over 11 000 patients, and their projected primary completion dates suggest that patient TMB data will continue to accumulate through 2019 and beyond. Of the 54 trials, 37 investigate immune checkpoint inhibitors and TMB, and findings show that integration of TMB as a biomarker for response to immune checkpoint inhibitors in clinical trials is diversifying from mostly melanoma and NSCLC trials into a range of other tumor types, including endometrial, colorectal, urothelial, and breast cancers . These findings underlie expectations that diagnostic assessment of TMB could provide benefit across many tumor types.…”
Section: The Future Clinical Landscape Of Tmbmentioning
confidence: 99%
“…Despite the current uncertainty regarding molecular markers such as MDM2 amplification and EGFR alterations that may predict HPD , the use of genomic aberrations as biomarkers for immunotherapy response pattern has been previously established . Indeed, although genomics and immunotherapy are often considered as separate fields, in reality, they are tightly linked .…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
“…Indeed, although genomics and immunotherapy are often considered as separate fields, in reality, they are tightly linked . There are various genomic aberrations that correlate with immunotherapy response, including (but not limited to) (A) mismatch repair gene defects that result in high microsatellite instability (MSI), (B) high tumor mutational burden (TMB), (C) PBRM1 and CDK12 mutations, and (D) PD‐L1 amplification . Other biomarkers include high PD‐L1 protein expression, gut microbiome, and POLE , ATM (TMB‐mediated), ATR (TMB‐mediated), and CDK12 mutations, which have been shown to predict response to immunotherapy .…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%